2014
DOI: 10.1055/s-0034-1372514
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Outcome after Extra-Articular Colles Fractures with Simultaneous Moderate Scapholunate Dissociation

Abstract: Background?An increased scapholunate gap is sometimes seen in patients with a distal radial fracture. The question remains as to whether this represents a scapholunate ligament injury that requires treatment. Questions/purposes?We wished to examine the natural history of an increased scapholunate gap in patients following an extra-articular distal radial fracture. Patients and Methods?We reviewed 260 patients who had sustained a distal radial fracture at a mean of 6.2 (2.7?11.9) years previously and identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…These findings were confirmed by Finsen et al . that defined SLD as a SLI ≥2mm in conventional radiographs of extra-articular distal radius fractures and evaluated the outcomes of 12 patients after a mean follow-up of 6 years [ 45 ]. They concluded that the outcomes with or without SLD were similar, although statistical analysis was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were confirmed by Finsen et al . that defined SLD as a SLI ≥2mm in conventional radiographs of extra-articular distal radius fractures and evaluated the outcomes of 12 patients after a mean follow-up of 6 years [ 45 ]. They concluded that the outcomes with or without SLD were similar, although statistical analysis was lacking.…”
Section: Discussionmentioning
confidence: 99%